The Human Resources Strategic Management - Emil Surlaru (Revista de Management Comparat International)
The most of the specialists value the role of the strategies and the tactics in modern societies development, including in the economic field, especially in increasing the companies effectiveness, but also for mezo, macro and worldwide economic levels. As response to some strong requirements, the strategies are used not only in economic field, but also in other ones: political, military, social, educational etc. In Romania, for each field of activity and each organization is necessary to ground, to elaborate, to adopt and to operate realistic scientific strategies; to accelerate this action in human resources field, the most important organizational resources, perhaps this is the most necessary issue. This article targets the following: I. to provide a short description of the strategic management and the strategy’s concepts; II. to emphasize/to highlight the foreign and Romanian specialists points of view out of strategic human resources management; III. to present author`s own considerations about strategic human resources management